The role of Nrf2 in the pathogenesis and treatment of ulcerative colitis - Peng, Shuai; Shen, Lei; Yu, Xiaoyun; Zhang, Li; Xu, Ke; Xia, Yuan; Zha, Lanlan; Wu, Jing; Luo, Hesheng (Frontiers in Immunology, 2023)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease involving mainly the colorectal mucosa and submucosa, the incidence of which has been on the rise in recent years. Nuclear factor erythroid 2-related factor 2 (Nrf2), a key transcription factor that regulates resistance to oxidative stress, plays an essential role in inducing antioxidant stress in the body and suppressing the inflammatory response. Several studies have demonstrated the involvement of the Nrf2 pathway in maintaining the development and normal function of the intestine, the development of UC, and UC-related intestinal fibrosis and carcinogenesis; meanwhile, therapeutic agents targeting the Nrf2 pathway have been widely investigated. This paper reviews the research progress of the Nrf2 signaling pathway in UC.